THE PERSPECTIVE OF ISLAMIC EDUCATION TO EDUCATIONAL METHODS - Andi Achruh; Muhammad Rusydi Rasyid; Nursalam Nursalam; M. Shabir U. (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:Islamic education is a system consisting of several important components that are interconnected. Among the existing components is the method of education. This study aimed to determine the learning methods used in Islamic education. This research used library research with a qualitative approach. Data sources were derived from various works of literature, including books, articles, newspapers, and documents. The data analysis techniques used were content and descriptive analyses. The finding indicated that several teaching methods used in Islamic education, including; 1) Lecture method, 2) Discussion method, 3) Demonstration method, 4) Insertion method, 5) Wrapping method, and 6) Inquiry method. Therefore, teachers are required to choose and determine the right method so that the achievement of educational goals can be carried out effectively and efficiently.Abstrak:Pendidikan Islam merupakan suatu sistem yang terdiri dari beberapa komponen penting yang saling berhubungan. Diantara komponen yang ada adalah metode pendidikan. Penelitian ini bertujuan untuk mengetahui metode pembelajaran yang digunakan dalam pendidikan Islam. Penelitian ini menggunakan penelitian kepustakaan dengan pendekatan kualitatif. Sumber data berasal dari berbagai karya kepustakaan, antara lain buku, artikel, surat kabar, dan dokumen. Teknik analisis data yang digunakan adalah analisis isi dan deskriptif. Hasil penelitian menunjukkan bahwa beberapa metode pengajaran yang digunakan dalam pendidikan Islam antara lain: 1) Metode Ceramah, 2) Metode Diskusi, 3) Metode Demonstrasi, 4) Metode Sisipan, 5) Metode Bungkus, dan 6) Metode Inquiry. Oleh karena itu, guru dituntut untuk memilih dan menentukan metode yang tepat agar pencapaian tujuan pendidikan dapat terlaksana secara efektif dan efisien.